Iot 기반 실내 공기오염 측정 시스템 - 김웅태(Ungtae Kim); 김용철(Yong-Chul Kim); 곽수영(Sooyeong Kwak) (한국콘텐츠학회 논문지, 16(2), 2016)
Many people interested in indoor air quality monitoring since they spend a majority of their time indoors such as homes and offices. This paper proposes the effective indoor air quality monitoring system and it can gauge carbon dioxide, particulate matter and VOCs(Volatile Organic Compounds) which can be harmful to humans. The proposed system is composed of three main modules which are device, web server, and mobile application. In order to evaluate the performance, we tested two cases which are candle and smoke. We monitor the condition of indoor air quality with our mobile application. Also, we developed the information graphics to compare the condition of air quality between indoor and outdoor and this mobile application improves usability. 사람들이 집, 회사 등에서의 실내생활이 증가함에 따라 실내 공기오염에 대한 관심도가 높다. 본 논문에서는 실내 공기오염 중 인체에 가장 영향을 많이 미치는 이산화탄소, 미세먼지, 생활용품에서 발생되는 휘발성유기화합물(VOCs)를 측정할 수 있는 실내 공기오염 측정 시스템을 제안한다. 제안된 시스템은 실내 공기오염을 측정하는 디바이스, 정보를 저장하고 전송 할 수 있는 웹서버, 오염정보를 확인할 수 있는 안드로이드 어플리케이션으로 구성되어 있다. 본 시스템의 성능 확인을 위하여 초와, 담배연기 두 가지 시료의 실험을 통해 실내 공기 상태 변화를 어플리케이션으로 확인하였다. 또한, 외부 대기 상태와 디바이스로부터 측정된 내부 대기 상태를 비교할 수 있도록 시각화함으로써 사용자의 편의성을 증대시킬 수 있을 것으로 판단된다.